Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(f\left(x\right)=x+\dfrac{\sqrt{x}}{x+1}\Rightarrow f'\left(x\right)=1+\dfrac{1-x}{2\sqrt{x}\left(x+1\right)^2}\)
\(f'\left(x\right)-1>0\Leftrightarrow\dfrac{1-x}{2\sqrt{x}\left(x+1\right)^2}>0\)
\(\Rightarrow0< x< 1\)
\(y'=x^2-2x+m\)
\(y'\ge0\) ; \(\forall x\in\left(1;3\right)\Leftrightarrow x^2-2x+m\ge0\) ;\(\forall x\in\left(1;3\right)\)
\(\Leftrightarrow m\ge\max\limits_{\left(1;3\right)}\left(-x^2+2x\right)\)
Xét hàm \(f\left(x\right)=-x^2+2x\) trên \(\left(1;3\right)\)
\(-\dfrac{b}{2a}=1\) ; \(f\left(1\right)=1\) ; \(f\left(3\right)=-3\)
\(\Rightarrow m\ge1\)
\(y'=4mx^3+2mx=2mx\left(2x^2+1\right)\)
Do \(2x\left(x^2+1\right)>0\) ;\(\forall x>0\)
\(\Rightarrow y'\ge0\) ;\(\forall x>0\) khi và chỉ khi \(m>0\)
\(y'=\dfrac{-m^2-1}{\left(x-m\right)^2}\)
\(y'< 0\) ;\(\forall x\in\left(0;1\right)\Leftrightarrow\left[{}\begin{matrix}m\ge1\\m\le0\end{matrix}\right.\)
\(y'=\dfrac{\left(2x-m\right)\left(x^2+1\right)-2x\left(x^2-mx+m\right)}{\left(x^2+1\right)^2}=\dfrac{2x-mx^2-m+2mx^2-2mx}{\left(x^2+1\right)^2}=\dfrac{mx^2+2\left(1-m\right)x-m}{\left(x^2+1\right)^2}\)
\(y'=0\Leftrightarrow mx^2+2\left(1-m\right)x-m=0\)
Xet \(m=0\) ko thoa man pt
Xet \(m\ne0\)
\(\left\{{}\begin{matrix}\Delta'>0\\\dfrac{2\left(m-1\right)}{m}=3\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\left(1-m\right)^2+m^2>0\left(ld\right)\\m=-2\end{matrix}\right.\Rightarrow m=-2\)
`f'(x) = x^2 - 4x+m`
`f'(x) >=0 <=>x^2-4x+m>=0`
`<=> \Delta' >=0`
`<=> 2^2-1.m>=0`
`<=> m<=4`
Vậy....
\(f'\left(x\right)=x^2+2\left(m-2\right)x+9\)
Để \(f'\left(x\right)\ge0\) \(\forall x\Leftrightarrow\Delta'\le0\Leftrightarrow\left(m-2\right)^2-9\le0\)
\(\Leftrightarrow-3\le m-2\le3\Leftrightarrow-1\le m\le5\)
\(y'=x^2-2mx+m\)
\(y'\ge0\Leftrightarrow\left\{{}\begin{matrix}a>0\\\Delta'\le0\end{matrix}\right.\Leftrightarrow m^2-m\le0\Leftrightarrow0\le m\le1\)
\(y'=\dfrac{2x^2-x-x^2+x-1}{\left(x^2-x+1\right)^2}=\dfrac{x^2-1}{\left(x^2-x+1\right)^2}\)
\(\dfrac{2x^3-2x}{\left(x^2-x+1\right)^2}-3.\dfrac{x^2}{\left(x^2-x+1\right)^2}\ge0\)
\(\Leftrightarrow2x^3-2x-3x^2\ge0\Leftrightarrow x^2+2x\le0\Leftrightarrow x\left(x+2\right)\le0\)
\(\Leftrightarrow-2\le x\le0\)
em cam on ạ